NASH/NAFLD-Related Hepatocellular Carcinoma: An Added Burden - Doina Georgescu; Daniel Florin Lighezan; Ciprian Ilie Rosca; Daciana Nistor; Oana Elena Ancusa; Ioana Suceava; Mihaela Adela Iancu; Nilima Rajpal Kundnani (Life, 2023)
Hepatocellular carcinoma (HCC) is the most frequently found primary malignancy of the liver, showing an accelerated upward trend over the past few years and exhibiting an increasing relationship with metabolic syndrome, obesity, dyslipidemia and type 2 diabetes mellitus. The connection between these risk factors and the occurrence of HCC is represented by the occurrence of non-alcoholic fatty liver disease (NAFLD) which later, based on genetic predisposition and various triggers (including the presence of chronic inflammation and changes in the intestinal microbiome), may evolve into HCC. HCC in many cases is diagnosed at an advanced stage and can be an incidental finding. We present such a scenario in the case of a 41-year-old male patient who had mild obesity and mixed dyslipidemia, no family or personal records of digestive pathologies and who recently developed a history of progressive fatigue, dyspepsia and mild upper abdominal discomfort initially thought to be linked to post-COVID syndrome, as the patient had COVID-19 pneumonia a month prior. The abdominal ultrasound revealed a mild hepatomegaly with bright liver aspect of the right lobe (diffuse steatosis), a large zone of focal steatosis (segments IV, III and II) and a left lobe tumoral mass, highly suggestive of malignancy. Point shear wave elastography at the right lobe ruled out an end-stage chronic liver disease. Additional laboratory investigations, imaging studies (magnetic resonance imaging) and histopathological examination of liver fragments confirmed a highly aggressive HCC, with poorly differentiation-G3, (T4, N 1M 0) and stage IVA, associated with nonalcoholic steatohepatitis (NASH). A sorafenib course of treatment was attempted, but the patient discontinued it due to severe side effects. The subsequent evolution was extremely unfavorable, with rapid degradation, a few episodes of upper digestive bleeding, hepatic insufficiency and mortality in a couple of months. Conclusions: Diagnosis of NASH-related HCC is either an accidental finding or is diagnosed at an advanced stage. In order to earn time for a proper treatment, it becomes important to diagnose it at an early stage, for which regular check-ups should be performed in groups having the risk factors related to it. Patients suffering from obesity and mixed dyslipidemia should undergo periodic abdominal ultrasound examinations. This should be emphasized even more in the cases showing NASH. Complaints of any kind post-COVID-19 should be dealt with keenly as little is yet known about its virulence and its long-term side effects.